Effect of rear surface fields on hot, refluxing and escaping electron populations via numerical simulations. (2019) - Rusby, D. R.; Armstrong, C. D.; Scott, G. G.; King, M.; McKenna, P.; Neely, D.
Abstract : After a population of laser-driven hot electrons traverses a limited thickness solid target, these electrons will encounter the rear surface, creating TV/m fields that heavily influence the subsequent hot-electron propagation. Electrons that fail to overcome the electrostatic potential reflux back into the target. Those electrons that do overcome the field will escape the target. Here, using the particle-in-cell (PIC) code EPOCH and particle tracking of a large population of macro-particles, we investigate the refluxing and escaping electron populations, as well as the magnitude, spatial and temporal evolution of the rear surface electrostatic fields. The temperature of both the escaping and refluxing electrons is reduced by 30%–50% when compared to the initial hot-electron temperature as a function of intensity between $10^{19}$ and $10^{21}~~\text{W}/\text{cm}^{2}$ . Using particle tracking we conclude that the highest energy internal hot electrons are guaranteed to escape up to a threshold energy, below which only a small fraction are able to escape the target. We also examine the temporal characteristic of energy changes of the refluxing and escaping electrons and show that the majority of the energy change is as a result of the temporally evolving electric field that forms on the rear surface.